Relation Between the Mechanical Properties of Muscles and Their Structure on the Molecular Level - Skubiszak, L.; Kowalczyk, L. (Engineering Transactions, 2015)
Mechanical properties of the vertebrate skeletal muscles are satisfactorily described on the basis of a new model of the myosin molecule packing into the thick filament.